Impact of hybridization on specific capacitance in hybrid NiO/V2O5@graphene composites as advanced supercapacitor electrode materials - Konda Shireesha; Shilpa Chakra Chidurala (Applied Surface Science Advances, 2022)
Currently, hybrid composites are considered promising materials in energy applications. Among various approaches for synthesizing hybrid composites, the solution combustion approach has attracted significant research interest worldwide due to its high versatility, efficiency, simplicity, scalability, reproducibility, and cost-effectiveness. Further, solution combustion synthetic techniques have recently been regarded as one of the more facile methods for developing effective supercapacitor electrodes. This paper provides the synthesis of vanadium pentoxide (V2O5), nickel oxide-vanadium pentoxide (NiO/ V2O5), and nickel oxide-vanadium pentoxide-Graphene (NiO/ V2O5@Graphene) nano-composites using solution combustion method. The importance of the hybridization of transition metal oxide with other-transition metal oxide and carbon derivatives is studied systematically. The obtained materials are characterized by X-ray diffraction, UV-Visible spectroscopy, Fourier transform infrared spectroscopy, Field emission scanning electron microscopy, Energy-dispersive X-ray analysis, Cyclic voltammetric analysis, Galvanostatic charge-discharge, and Electrochemical impedance. The average crystalline sizes are calculated as 27 nm, 24 nm, and 14 nm for V2O5, NiO/ V2O5, and NiO/ V2O5@Graphene nano-composites. The UV-Visible, Fourier transform infrared, and Energy-dispersive X-ray spectroscopy analysis confirms the formation of synthesized materials. Field emission scanning electron microscopy provides the distribution of NiO/ V2O5 nano-composite over the graphene sheet. The electrochemical performance of V2O5 is improved drastically with the simultaneous hybridization of two metal oxides. Further, the addition of graphene makes a small enhancement in the specific capacitance of the nano-composites. The order of specific capacitance is V2O5 (328 F/g) ˂ NiO/V2O5 (918 F/g) ˂ NiO/V2O5@Graphene (939 F/g). The solution resistance and charge transfer resistance of the modified electrodes are in the order of V2O5 (1.59 Ω) ˃ NiO/V2O5 (0.85 Ω) ˃ NiO/V2O5@Graphene (0.73 Ω) and V2O5 (5.66 Ω) ˃ NiO/V2O5 (1.35 Ω) ˃ NiO/V2O5@Graphene (0.17 Ω) respectively, which supports the enhancement in specific capacitance upon hybridization. The obtained materials are cost-effective, low-toxic, and efficient, hence would be appropriate for industrial use.